Sketsmasa's Framing of Sukarno and Suharto in 1957-1968: A Study of Media Framing in the Authoritarian Era - Firdiyansyah, Mohammad Masrudin; Rizky, Nabil Bahar (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This article aims to explain Sketsmasa magazine's framing of the Old and New Order rulers. The method used in this research is the historical method. The results show that Sketsmasa positively framed the Old and New Order governments because the government banned media that threatened their status quo. Sketsmasa's positive framing of the Old Order ruler, Sukarno, was by conveying Sukarno's outstanding leadership and correcting slanders against Sukarno that could defame him. During the New Order, Sketsmasa framed differently. Sketsmasa's framing was not only in the form of positive things about the then ruler, Soeharto, but also negative things about the previous ruler, Soekarno. Sketsmasa attacked Sukarno's personality and showed the crimes of the Old Order that had never been shown by Sketsmasa before. The aim was to create the impression in society that Soeharto was the savior of the abuses committed by Sukarno during the Old Order.